PELATIHAN PENYUSUNAN LAPORAN KEUANGAN BUMDES (BADAN USAHA MILIK DESA): Studi Pada Desa Lumban Pea Timur Kabupaten Toba - Arthur Simanjuntak; Melanthon Rumapea; Septony B. Siahaan; Dompak Pasaribu; Lamria Sagala; Mitha Christina Ginting; Mulatua P. Silalahi; Junika Napitupulu; Farida Sagala; Rike Y. Panjaitan; Duma Rahel Situmorang; Jimmy F. Naibaho; Putri Jesica Sitorus; Gracesiella Y. Simanjuntak (Jurnal Pengabdian Pada Masyarakat METHABDI, 2022)
Badan Usaha Milik Desa (hereinafter referred to as BUMDesa Lumbung Parsaulian) are one of the alternatives to improving the rural economy, especially in Lumban Pea Timur Village, Toba Regency. Unfortunately, the position of BUMDesa Lumbung Parsaulian is not running as expected to boost the regional economy. Another more complex issue is choosing the type of company they will run and how to make financial reports to outside parties that help fund the business they started. Training on the Preparation of BUMDesa Lumbung Parsaulian Financial Statements in Lumban Pea Timur Village, Balige District, Toba Regency is in accordance with the applicable SAK - ETAP, so that the financial statements of BUMDesa Lumbung Parsaulian in Lumban Pea Timur Village, Balige District, Toba Regency are prepared properly and correctly and can be accounted for to stakeholders.